2021
DOI: 10.3389/fpsyt.2021.630697
|View full text |Cite
|
Sign up to set email alerts
|

Examining Associations Between Child Abuse and Neglect Experiences With Emotion Regulation Difficulties Indicative of Adolescent Suicidal Ideation Risk

Abstract: Objective: Preliminary work indicates one specific aspect of emotion dysregulation (i.e., limited access to emotion regulation strategies) uniquely associates with adolescent suicide ideation. An optimal score cut point on a measure of this emotion dysregulation impairment has been identified to indicate risk for past-year suicidal ideation. Examining types of child abuse and neglect associated with being above cut-off on this measure may point to interactive environmental effects associated with subsequent ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Intriguingly, in a longitudinal study with a sizable sample (i.e., 5423), Wu et al [ 39 ] found that in a mediation model, emotion reactivity (an index of DER) leads to depression, and depression leads to SI, which is precisely consistent with our findings and model. Consistently and particularly, Hatkevich et al [ 43 ] researched different forms of childhood abuse and found that compared to other forms of abuse and neglect, emotional abuse may be more strongly associated with having restricted access to emotion regulation strategies during adolescence, which is a condition suggestive of a higher risk of SI. Demirci also reported associations between childhood sexual abuse, DER, and diverse psychiatric conditions [ 88 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Intriguingly, in a longitudinal study with a sizable sample (i.e., 5423), Wu et al [ 39 ] found that in a mediation model, emotion reactivity (an index of DER) leads to depression, and depression leads to SI, which is precisely consistent with our findings and model. Consistently and particularly, Hatkevich et al [ 43 ] researched different forms of childhood abuse and found that compared to other forms of abuse and neglect, emotional abuse may be more strongly associated with having restricted access to emotion regulation strategies during adolescence, which is a condition suggestive of a higher risk of SI. Demirci also reported associations between childhood sexual abuse, DER, and diverse psychiatric conditions [ 88 ].…”
Section: Discussionmentioning
confidence: 91%
“…Hatkevich et al [ 42 ] found among adolescent inpatients that limited access to emotion regulation strategies, difficulties in impulse control, and mood disorder diagnosis were significantly associated with past-year SI. Hatkevich et al [ 43 ] demonstrated that emotional abuse might be differentially related to experiencing limited access to emotion regulation strategies at the level indicative of SI risk. Thus, SI may stem from ChT and, subsequently, the emotional dysregulation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that sexual abuse has a stronger association with suicide ideation than physical abuse or witnessing violence [26]. In addition, it is suggested that although all types of child abuse affect adversely on child development, emotional abuse has especially detrimental and long-lasting effects on mental health and suicidality [27]. Autonomy can serve as a protective resource because it allows adolescents to develop their own effective coping strategies for handling life stressors.…”
Section: Suicidal Ideation From a Socio-ecological Approachmentioning
confidence: 99%
“…However, relatively little work has specifically investigated adolescents engaging in SI. One neuro-cognitive risk factor associated with SI and potentially suicidal behavior (SB) is emotion dysregulation [8][9][10][11]. Older adolescents/young adults who report more emotion regulation difficulties show greater SI even after accounting for depression symptoms [12].…”
Section: Introductionmentioning
confidence: 99%